Atrial mechanical hypofunction after electrical cardioversion of persistent or long-lasting persistent atrial fibrillation: a retrospective cohort study - De Vecchis, Renato; Paccone, Andrea; Di Maio, Marco (Monaldi Archives for Chest Disease, 2019)
In the present retrospective cohort study, we have evaluated the missed or delayed atrial mechanical recovery in a population of patients with persistent or long-lasting persistent AF who achieved restoration of sinus rhythm on the ECG by electrical cardioversion (ECV). The endpoint of our study was the failure to recover the normal mechanics of the left atrium. Inclusion criterion was the persistent or long-lasting persistent atrial fibrillation successfully treated by means of ECV , provided that a pertinent documentation was made available, comprising ECG, conventional 2D echo-color-Doppler and speckle tracking echocardiography(STE) evaluation, with also a STE assessment of the atria at the days 1, 30 and 90 from the ECV freely available within the clinical record of the patient. Out of a total of 80 patients with persistent or long-standing persistent AF, retrospectively enrolled, as many as 22.5% of them did not achieve the normalization of their atrial STE profile, even though they had been converted to sinus rhythm on the ECG by means of ECV. The building of ROC curves allowed us to establish that early measurements of global atrial strain could serve to predict both the risk of failure to recover the atrial mechanical function and the one of AF relapses over a 12 month follow-up. The values of 18% and 17% were also calculated to serve as cut off values, respectively, for the risk of atrial mechanical dysfunction and for the risk of AF relapses over a 12 month follow-up. Failure to recover the atrial reservoir function can accompany a restoration of sinus rhythm on the ECG in patients with long-standing persistent AF. In this case, a serial STE evaluation could be useful to evaluate the atrial hypofunction over time.